Pengaruh Asimetri Informasi Terhadap Income Smoothing dengan Good Corporate Governance sebagai Pemoderasi - Afifah Dwi Aprillia; Etty Gurendrawati; Hafifah Nasution (Indo Publishing, 2025)
This reasearch aims to determine the effect of information asymmetry on income smoothing with good corporate governance as a moderator. The research method used is quantitative research. The unit of analysis in this study is non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) throughout 2019–2023. The sample selection method used is purposive sampling and selected 21 companies with a total sample of 105 research data. The analysis technique in this study uses descriptive statistical analysis and logistic regression analysis with moderation with IBM SPSS Statistics software version 27 and a significance level of 5%. Tests carried out include multicollinearity tests, overall model test, model fit test, goodness of fit test, coefficient of determination test, model accuracy test, and Wald test. The results of this study indicate that information asymmetry has no effect on income smoothing, independent commissioners cannot moderate the effect of information asymmetry on income smoothing, audit committees can moderate the effect of information asymmetry on income smoothing, and managerial ownership can moderate the effect of information asymmetry on income smoothing. In future research, it is hoped that other variables such as company size, debt level, and audit quality can be used. In addition, further research can examine other company sectors such as the banking sector, financial sector, and mining sector